PERILAKU PENCEGAHAN DEMAM BERDARAH OLEH MASYARAKAT DI MUARA FAJAR BARAT TAHUN 2023 - Roni Saputra (LPPM Universitas Abdurrab, 2024)
ABSTRACT Dengue hemorrhagic fever is by far one of the diseases that have become an international health problem. Dengue cases have increased over the past 10 years, with 500,000 dengue cases and more than 20,000 deaths each year. The purpose of this study was to find out how knowledge, attitudes and actions of the community in efforts to prevent dengue fever in Muara Fajar Barat. The type of research in this study is quantitative research with a cross sectional approach. This research was conducted in Pekanbaru, Muara Fajar Barat Village, Rumbai District, Pekanbaru Regency, Riau Province, from August 2023 to January 2023. The population in this study is the entire community in Muara Fajar Barat Village. The sample in the study amounted to 300 people. Data were collected using questionnaires and analyzed using spss statistical tests. The results of the study were obtained by the majority of respondents with moderate knowledge about dengue prevention, namely 126 (42%), positive attitudes of 182 (60.7%), and less actions as much as 289 (96.3%). The conclusion of the study is that the most DHF prevention behavior is a lack of action regarding DHF prevention. It is expected that health workers will be more proactive in providing counseling or health education about DHF and its prevention, because actions are influenced by public knowledge Keywords : Knowledge, Attitude, Action